2023
DOI: 10.3389/fchem.2023.1177680
|View full text |Cite
|
Sign up to set email alerts
|

Michael addition of P-nucleophiles to azoalkenes provides simple access to phosphine oxides bearing an alkylhydrazone moiety

Abstract: β-Hydrazonophosphine oxides are precursors of useful organophosphorus compounds, including phosphorylated N-heterocycles, α-aminophosphonates, and vinylphosphonates. In this work, a general transition metal-free synthesis of β-hydrazonophosphine oxides was developed. The method relies on the Michael addition of phosphine oxides R2P(O)H to reactive azoalkenes (1,2-diaza-1,3-butadienes), which are generated in situ from α-halohydrazones and Hunig’s base. The reaction stereoselectively leads to Z-isomers of β-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…A Michael addition follows by the loss of CO2 is consistent with fragment 5b at m/z 221.2 in its keto form as shown in Scheme 14 [54]. In this case, the double bond between C-2 and C-3 is the nucleophile and the double bond between C-2′-C-3′ is the Michael ac- A Michael addition follows by the loss of CO2 is consistent with fragment 5b at m/z 221.2 in its keto form as shown in Scheme 14 [54]. In this case, the double bond between C-2 and C-3 is the nucleophile and the double bond between C-2′-C-3′ is the Michael acceptor.…”
Section: Supplementary Materialssupporting
confidence: 60%
See 2 more Smart Citations
“…A Michael addition follows by the loss of CO2 is consistent with fragment 5b at m/z 221.2 in its keto form as shown in Scheme 14 [54]. In this case, the double bond between C-2 and C-3 is the nucleophile and the double bond between C-2′-C-3′ is the Michael ac- A Michael addition follows by the loss of CO2 is consistent with fragment 5b at m/z 221.2 in its keto form as shown in Scheme 14 [54]. In this case, the double bond between C-2 and C-3 is the nucleophile and the double bond between C-2′-C-3′ is the Michael acceptor.…”
Section: Supplementary Materialssupporting
confidence: 60%
“…A Michael addition follows by the loss of CO 2 is consistent with fragment 5b at m / z 221.2 in its keto form as shown in Scheme 14 [ 54 ]. In this case, the double bond between C-2 and C-3 is the nucleophile and the double bond between C-2′-C-3′ is the Michael acceptor.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previously we showed that the slow addition of αhalohydrazones to a THF solution of a sterically encumbered Hunig's base ( i Pr 2 NEt) provides a mild way to generate azoalkenes in a low stationary concentration for efficient coupling with nucleophiles. 12 Therefore, in the initial experiment, model α-bromoacetophenone hydrazone 1a was slowly added to a solution containing phenylacetylene (2a) (1.5 equiv), i Pr 2 NEt (3.0 equiv), and CuI (1.0 equiv) in THF at 0 °C (Table 1). Analysis of the crude product after workup showed the presence of alkynyl-substituted hydrazone 3a (78% yield).…”
mentioning
confidence: 99%
“…The proposed mechanism for the Cu-catalyzed alkynylation of α-halohydrazones 1 is shown in Scheme 4. 1,4-Dehydrohalogenation of halohydrazones 1 with a base (e.g., i Pr 2 NEt) generates azoalkenes 12 The latter are known to form N,O-chelatates with copper salts resulting in some stabilization of the labile intermediates A. 5h,j,k,15 Two conformations (transoid and cisoid) with respect to the azadiene moiety are possible for the Cu−A chelate.…”
mentioning
confidence: 99%